Silicon on silicon dioxide slot waveguide evanescent field gas absorption sensor. Issue 2 (19th January 2018) - Butt, M. A.; Khonina, S. N.; Kazanskiy, N. L.
Abstract: Several trace gases such as H2 O, CO, CO2, NO, N2 O, NO2 and CH4 strongly absorb in the mid-IR spectral region due to their fundamental rotational and vibrational transitions. In this work, we propose an evanescent field absorption gas sensor based on silicon/silicon dioxide slot waveguide at 3.39 μm for sensing of methane gas. These waveguides can provide the highest evanescent field ratio (EFR) > 47% with adequate dimensions. Higher EFR values often come at an expense of higher propagation losses. These waveguides have relatively higher losses as compared to conventional waveguides, such as rib and slab waveguides, as these fundamental losses are static and the proposed sensing mechanism is established on the incremental loss due to the absorption of the gas. Therefore, incident power can always be incremented to compensate the waveguide losses.